A procedure to determine the planar integral spot dose values of proton pencil beam spots - Anand, Aman (American Association of Physicists in Medicine, 2012)
Purpose: Planar integral spot dose (PISD) of proton pencil beam spots (PPBSs) is a required input parameter for beam modeling in some treatment planning systems used in proton therapy clinics. The measurement of PISD by using commercially available large area ionization chambers, like the PTW Bragg peak chamber (BPC), can have large uncertainties due to the size limitation of these chambers. This paper reports the results of our study of a novel method to determine PISD values from the measured lateral dose profiles and peak dose of the PPBS. Methods: The PISDs of 72.5, 89.6, 146.9, 181.1, and 221.8 MeV energy PPBSs were determined by area integration of their planar dose distributions at different depths in water. The lateral relative dose profiles of the PPBSs at selected depths were measured by using small volume ion chambers and were investigated for their angular anisotropies using Kodak XV films. The peak spot dose along the beam’s central axis (D(0)) was determined by placing a small volume ion chamber at the center of a broad field created by the superposition of spots at different locations. This method allows eliminating positioning uncertainties and the detector size effect that could occur when measuring it in single PPBS. The PISD was then calculated by integrating the measured lateral relative dose profiles for two different upper limits of integration and then multiplying it with corresponding D(0). The first limit of integration was set to radius of the BPC, namely 4.08 cm, giving PISD(RBPC). The second limit was set to a value of the radial distance where the profile dose falls below 0.1% of the peak giving the PISD(full). The calculated values of PISD(RBPC) obtained from area integration method were compared with the BPC measured values. Long tail dose correction factors (LTDCFs) were determined from the ratio of PISD(full)/PISD(RBPC) at different depths for PPBSs of different energies. Results: The spot profiles were found to have angular anisotropy. This anisotropy in PPBS dose distribution could be accounted in a reasonable approximate manner by taking the average of PISD values obtained using the in-line and cross-line profiles. The PISD(RBPC) values fall within 3.5% of those measured by BPC. Due to inherent dosimetry challenges associated with PPBS dosimetry, which can lead to large experimental uncertainties, such an agreement is considered to be satisfactory for validation purposes. The PISD(full) values show differences ranging from 1 to 11% from BPC measured values, which are mainly due to the size limitation of the BPC to account for the dose in the long tail regions of the spots extending beyond its 4.08 cm radius. The dose in long tail regions occur both for high energy beams such as 221.8 MeV PPBS due to the contributions of nuclear interactions products in the medium, and for low energy PPBS because of their larger spot sizes. The calculated LTDCF values agree within 1% with those determined by the Monte Carlo (MC) simulations. Conclusions: The area integration method to compute the PISD from PPBS lateral dose profiles is found to be useful both to determine the correction factors for the values measured by the BPC and to validate the results from MC simulations.